Susceptibility to stress corrosion cracking of fe-35mn alloy under a pseudo-physiological condition - Hermawan, Hendra (2013)
Biodegradable metals have been proposed for temporary implants such as coronary artery stent and internal bone fixators. During implantation, a stent is inserted and expanded by using a catheter into a narrowed coronary artery and is subjected to mechanical stress in a corrosive body fluid environment, a condition where stress corrosion cracking may occur. This letter reports an experimental work to verify the susceptibility of Fe-35Mn alloy, a proposed alloy for biodegradable coronary stent, to stress corrosion cracking under a pseudo-physiological condition.